26-h+7h-12=-2h-19-3h

Simple and best practice solution for 26-h+7h-12=-2h-19-3h equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 26-h+7h-12=-2h-19-3h equation:


Simplifying
26 + -1h + 7h + -12 = -2h + -19 + -3h

Reorder the terms:
26 + -12 + -1h + 7h = -2h + -19 + -3h

Combine like terms: 26 + -12 = 14
14 + -1h + 7h = -2h + -19 + -3h

Combine like terms: -1h + 7h = 6h
14 + 6h = -2h + -19 + -3h

Reorder the terms:
14 + 6h = -19 + -2h + -3h

Combine like terms: -2h + -3h = -5h
14 + 6h = -19 + -5h

Solving
14 + 6h = -19 + -5h

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '5h' to each side of the equation.
14 + 6h + 5h = -19 + -5h + 5h

Combine like terms: 6h + 5h = 11h
14 + 11h = -19 + -5h + 5h

Combine like terms: -5h + 5h = 0
14 + 11h = -19 + 0
14 + 11h = -19

Add '-14' to each side of the equation.
14 + -14 + 11h = -19 + -14

Combine like terms: 14 + -14 = 0
0 + 11h = -19 + -14
11h = -19 + -14

Combine like terms: -19 + -14 = -33
11h = -33

Divide each side by '11'.
h = -3

Simplifying
h = -3

See similar equations:

| 5x+15+2x=42+4x | | -36-8x=2(x-3) | | 4x+16=4x+16 | | 2(2x+8)=-2(2x-8) | | 4c+3d=-9 | | x^2-7x+4=2x+4 | | -7(a+6)=-3(4a+4) | | -6x+8=2x+6 | | 2(2x-8)=2(-2x-8) | | 4(x+2)-3x=3x+5 | | 19x+10=12x+45 | | x+2=2x+12 | | 8(s-2)=5s+11 | | 41x-1=x-121 | | 5-5n+4(3n-2)=39 | | 4(6x-2)=2(3x+5) | | 2x+1y=29 | | -4d(2d+3)=3(-4d-4) | | 23=8x | | 5v^2-10v-40=0 | | (2x+1)-2(x-5)+6=3x(x+1)+(x-1)+23 | | 4(7v-2)-7=4(1+7v) | | 4k(3+k)=-(2k+3) | | -9(z+5)=0 | | -9(z+6)=0 | | x(x-3)-x(x+5)+6=-2 | | 1-7n-2n=-8 | | 7-a=15a-2a | | -16x^2+3x+1.3=0 | | (23+5x)=(14x-3) | | 3(n-8)=4(n+2) | | (2n+5)(2n+3)=0 |

Equations solver categories